PEMIKIRAN HUKUM ISLAM MUHAMMAD SYAHRUR (TEORI HUDUD) - Kholidah Kholidah (IAIN Padangsidimpuan, 2016)
Muhammad Syahrur one of figure reformer thought Islamic law controversial. hers mind be welcome the pros and cons of various parties. some support because that his mind giving big contribution ini fiqh enrichment. with the theory of Hudud, Muhammad Syahrur has done of deconstruction and reconstruction to methodology ijtihad, especially ayat-ayat muhkamat, so that the teaching of Islam is a relevant to space and time. but not less that gave a negative respons, because methodologically in up Syahrur having no buttom of a study Islam been undertaken by the clergy. Muhammad Syahrur has done interpretation of the laws different at all with the mufassir and the fuqaha conventional and has given birth to legal products that opposite law already raw so far. Her trends to the philosophy of Marxism and to the using hermeneutika philology have provoked many mistakes in producing Islamic law.